1978
DOI: 10.1136/gut.19.4.277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a protein meal, intraduodenal HCl, and oleic acid on portal and peripheral venous secretin and on pancreatic bicarbonate secretion.

Abstract: SUMMARYWe have studied the effect of a protein meal on secretin (IRS) concentration in dogs and humans using a radioimmunoassay of improved sensitivity (8 pg/ml). After a meal, pancreatic bicarbonate secretion (PBS) increased markedly and proximal duodenal pH decreased from 6-2 to 4-3. Portal and peripheral IRS concentrations, however, remained unchanged in eight dogs and five patients with cirrhosis of the liver. Similarly, an alkaline solution of sodium oleate (pH 9-2) stimulated PBS but not IRS. Intraduoden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…Many data on the effects of different duodenal hydrochloric acid loads on exocrine pancreatic secretion have been published (Meyer, Way & Grossman, 1970;Schaffalitzky de Muckadell, Fahrenkrug & Holst, 1977;Boden, Wilson, Essa-Koumar & Owen, 1978;Garcia et al 1991). In our study, the maximum flow rates and bicarbonate output after intraduodenal perfusion of sodium carbonate were higher than those observed after a hydrochloric acid load of 18 mmol h-1.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Many data on the effects of different duodenal hydrochloric acid loads on exocrine pancreatic secretion have been published (Meyer, Way & Grossman, 1970;Schaffalitzky de Muckadell, Fahrenkrug & Holst, 1977;Boden, Wilson, Essa-Koumar & Owen, 1978;Garcia et al 1991). In our study, the maximum flow rates and bicarbonate output after intraduodenal perfusion of sodium carbonate were higher than those observed after a hydrochloric acid load of 18 mmol h-1.…”
Section: Discussioncontrasting
confidence: 46%
“…The release of secretin in response to intraduodenal perfusion of hydrochloric acid is well established (Isenberg, Cano & Bloom, 1977;Schaffalitzky de Muckadell et al 1977;Boden et al 1978;Otsuki, Sakamoto, Ohki, Yuu, Maeda & Baba, 1981). We have observed a clear dose-response relationship between the intraduodenal hydrochloric acid load and secretin levels in rabbit portal plasma (Garcia et al 1991) and have also recently demonstrated the release of secretin in response to the presence of some alkaline solutions in the rat duodenum (Garcia et al 1990).…”
Section: Atropine Effectmentioning
confidence: 54%
“…− and secretin levels increased immediately after instilling 0.1 N HCl into duodenum and jejunum of healthy volunteers 75,76 and a dose-response relationship of these effects has been demonstrated in dogs. 77 Infusions of up to 42 mmol of 0.1 N HCl in duodenum bulb were completely neutralized before reaching upper jejunum (the aspiration tip was positioned at the ligament of Treitz) of fasting healthy volunteers and the percentage of time at pH of less than 4.0 was only around 5%. 78 Also, the pH of buffered solutions of high-buffer capacity (stronger buffers than usually used for in vitro dissolution tests) infused into the upper jejunum of healthy subjects tended toward 6.0, regardless of the initial pH of the solution, 4.5 or 7.4.…”
Section: Hcomentioning
confidence: 99%
“…Some studies, however, have shown that intraduodenally given HCI has no effect on the release of PP in dogs (25). Intestinal acidification has been recognized as the primary secretagogue of the release of secretin (32,33). Intestinal acidification has been recognized as the primary secretagogue of the release of secretin (32,33).…”
Section: Discussionmentioning
confidence: 99%